Towards Therapeutic Delivery of Extracellular Vesicles: Strategies for In Vivo Tracking and Biodistribution Analysis - Giuliana Di Rocco; Silvia Baldari; Gabriele Toietta (Stem Cells International)
Extracellular vesicles (EVs), such as microvesicles and exosomes, are membranous structures containing bioactive material released by several cells types, including mesenchymal stem/stromal cells (MSCs). Increasing lines of evidences point to EVs as paracrine mediators of the beneficial effects on tissue remodeling associated with cell therapy. Administration of MSCs-derived EVs has therefore the potential to open new and safer therapeutic avenues, alternative to cell-based approaches, for degenerative diseases. However, an enhanced knowledge about in vivo EVs trafficking upon delivery is required before effective clinical translation. Only a few studies have focused on the biodistribution analysis of exogenously administered MSCs-derived EVs. Nevertheless, current strategies for in vivo tracking in animal models have provided valuable insights on the biodistribution upon systemic delivery of EVs isolated from several cellular sources, indicating in liver, spleen, and lungs the preferential target organs. Different strategies for targeting EVs to specific tissues to enhance their therapeutic efficacy and reduce possible off-target effects have been investigated. Here, in the context of a possible clinical application of MSC-derived EVs for tissue regeneration, we review the existing strategies for in vivo tracking and targeting of EVs isolated from different cellular sources and the studies elucidating the biodistribution of exogenously administered EVs.